1998
DOI: 10.1007/s003830050403
|View full text |Cite
|
Sign up to set email alerts
|

Median sternotomy for the resection of bilateral pulmonary metastases in children

Abstract: Childhood cancer often results in pulmonary metastases, and proper identification and prompt treatment of these lesions increases the survival of these patients. Between 21 May 1995 and 26 June 1996, nine children (five with osteosarcoma, two with Wilms' tumor, and one each with hepatoblastoma and an adrenocortical tumor) underwent median sternotomy at our institution for resection of bilateral pulmonary metastases. These five boys and four girls ranged in age from 2 to 16 years (median, 11 years). Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Our results confirmed this experience and corroborate the concept of using open surgery. Some authors recommend a median sternotomy for routine bilateral lung exploration [8]. In our and others [16] experience, a lateral thoracotomy allows a better access to basal and posteriorly located lung segments as well as to lymph nodes.…”
mentioning
confidence: 62%
“…Our results confirmed this experience and corroborate the concept of using open surgery. Some authors recommend a median sternotomy for routine bilateral lung exploration [8]. In our and others [16] experience, a lateral thoracotomy allows a better access to basal and posteriorly located lung segments as well as to lymph nodes.…”
mentioning
confidence: 62%
“…This approach allows for palpation of nodules in both lungs, which is paramount in identifying lesions that may not have been identified on CT [10,[13][14][15]. Computed tomography is considered the current radiographic gold standard in identifying and localizing metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found no increase in complications or mortality or decrease in overall survival [11]. More recently, several authors have described this approach in children as a safe method that provides simultaneous access to both hemithoraces with no increase in operative morbidity or mortality in children [13][14][15].…”
mentioning
confidence: 96%